2020
DOI: 10.1038/s41598-020-79206-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil fungal and bacterial communities in southern boreal forests of the Greater Khingan Mountains and their relationship with soil properties

Abstract: Little is known about the relationship between soil microbial communities and soil properties in southern boreal forests. To further our knowledge about that relationship, we compared the soil samples in southern boreal forests of the Greater Khingan Mountains—the southernmost boreal forest biome in the world. The forests can be divided into boardleaf forests dominated by birch (Betula platyphylla) or aspen (Populus davidiana) and coniferous forests dominated by larch (Larix gmelinii) or pine (Pinus sylvestris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…This study found that mining disturbance significantly reduced the levels of AK, which was significantly related to changes in the structure of both soil fungal and AMF communities, with a positive correlation with fungal community diversity. These results are consistent with the findings of Vuong et al [ 62 ].…”
Section: Discussionsupporting
confidence: 94%
“…This study found that mining disturbance significantly reduced the levels of AK, which was significantly related to changes in the structure of both soil fungal and AMF communities, with a positive correlation with fungal community diversity. These results are consistent with the findings of Vuong et al [ 62 ].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, Cortinarius, Piloderma , and Suillus were also found to be dominant, especially in boreal forests [ 68 , 71 , 72 ]. In addition, Meliniomyces have been observed to be able to form both ectomycorrhiza and ericoidmycorrhiza [ 76 , 77 ]. Notably, certain previously published studies have reported that the geographical region, the specific season, the dominant tree species, nutrient availability, and the physical and chemical properties of the soil and soil depth all significantly affected the composition of the fungal community in the soil [ 37 , 68 , 71 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different responses of bacterial and fungal communities were observed in the presence of wetland and upland vegetation (Hannula et al, 2019;Gschwend et al, 2021). Earlier investigations have confirmed that tree or plant species can contribute to differences in soil properties and, in turn, microbial communities (Samad et al, 2017;Vuong et al, 2020). Indeed, different plant species can produce various microbial resources through root exudates, root cap sloughing, and root turnover, and can be colonized by distinct 10.3389/fmicb.2023.1168653 Frontiers in Microbiology 14 frontiersin.org populations of more or less diverse microorganisms (Zhang et al, 2017;Gagnon et al, 2020b).…”
Section: Discussionmentioning
confidence: 93%